Determination of dislocation density in GaN layers using KOH defect MOVPE grown etching - Wellmann, Peter; Sakwe, Aloysius; Oehlschläger, Felix; Hoffmann, Veit; Zeimer, Ute; Knauer, Arne (Journal of Crystal Growth, 2008)
We report on molten KOH-based defect etching of GaN epitaxial layers for the quantitative determination of the dislocation density. Etching process parameters were established at 450 degrees C that are suitable to reveal threading edge and threading screw dislocations at the same time and, hence, allow for the quantitative determination of the total dislocation density in the metal organic vapor-phase epitaxy (MOVPE) grown GaN layers. The determined dislocation numbers in the 10(8)cm(-2) range are correlated (i) with the full-width half-maximum of rocking curves of the (3 0 (2) over bar) reflection and (ii) dark spots observed by cathodoluminescence of the etched GaN surfaces. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Defect etching; GaN; KOH